2015
DOI: 10.1108/whatt-06-2015-0031
|View full text |Cite
|
Sign up to set email alerts
|

Adapting evidence-based intervention in rural tourism policies

Abstract: This study aims to assess the possibility of adapting evidence-based policies in the daily operations of tour operators in Semporna, Sabah, Malaysia. This intervention is important, as on-site investigations reveal that operators are operating their businesses with little reference to the ecotourism policy guidelines. Design/methodology/approach This study adopted a full qualitative approach. In-depth interviews were conducted on tour operators in Semporna, while text mining was used to elicit data from the Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…Contrary to those observed in Semporna (Siow et al, 2015) , where most of the owner-manager of the tour operator are outsiders which bring the concern on economic leakage, whereas in Kuala Sepetang, most of the owner-manager consist of locals. This could be due to the local community's familiarity of the local environment, especially the mangrove and some of them is involving in fishing activity thus capable of operating a boat, enabling to providing boat service easily.…”
Section: Key Findingscontrasting
confidence: 58%
See 1 more Smart Citation
“…Contrary to those observed in Semporna (Siow et al, 2015) , where most of the owner-manager of the tour operator are outsiders which bring the concern on economic leakage, whereas in Kuala Sepetang, most of the owner-manager consist of locals. This could be due to the local community's familiarity of the local environment, especially the mangrove and some of them is involving in fishing activity thus capable of operating a boat, enabling to providing boat service easily.…”
Section: Key Findingscontrasting
confidence: 58%
“…Tourism is increasingly popular as being perceived an alternative strategy in achieving prodigious economic growth and social development in rural area (Okech et al, 2012;Siow et al, 2015). Particularly at places that experiencing rural decline or places where traditional rural industries face challenges, tourism provides an alternative strategy to diversified economy and alternative source of income.…”
Section: Introductionmentioning
confidence: 99%
“…Oswald et al [53] argued that the indigenous communities are highly dependent on natural resources but aggressive harvesting may cause the forest to fail to provide them with their daily requirements. Goodwin [50], Siow et al [54] and Nair et al [49] suggested that the government can assist the indigenous communities in providing them with the resources that are lacking to ensure tourism sustainability.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the application of the diagnostic by means of a case study, therefore, contribute to the existing literature on tourism development by giving insights in two ways: the possibilities of executing a tourism-driven growth diagnostic, and identifying the binding constraints for tourism-related growth in a specific case like North Macedonia. This study is also timely and relevant for tourism policy makers as there has been an increased desire for tools that can be used for evidence-based policy making (Siow et al, 2015). This paper is structured as follows.…”
Section: Introductionmentioning
confidence: 99%